In vitro propagation and evaluation of morphophysiologic parameters of grapevine rootstocks - Borghezan, Marcelo; Moraes, Liziane Kadine Antunes de; Moreira, Flávia Maia; Silva, Aparecido Lima da (Pesquisa Agropecuaria Brasileira, 2003)
Micropropagation of selected genotypes can be valuable to achieve demand for elite plants with genetic fidelity and high sanitary quality of grapevine (Vitis spp.) in Santa Catarina State, Brazil. The objective of this work was to propagate grapevine rootstocks in vitro and to evaluate important morphophysiologic parameters for the plants micropropagation and acclimatization. Axillary buds of the rootstocks grapevine VR043-43, VR039-16, Paulsen 1103, R110, SO4 and Kober 5BB were inoculated in DSD1 culture medium. Rates of 42% of explants were established in vitro. There was variation in growth, leaf area and dry weight among the genotypes. Paulsen 1103 revealed superior features in vitro for length of the stem (6.2 cm), biomass production (34.8 mg) and leaf area (18.1 cm2). The chlorophyll content showed variation among the rootstocks and the environment of the culture, ranging from 0.7 to 2.8 mg/g in fresh weight for R110 (in vitro) and VR043-43 (ex vitro), respectively. The highest (216.4/mm2) and the lowest (119.2/mm2) stomata number were shown by VR039-16 cultivated in vitro and by SO4 ex vitro, respectively. In the acclimatization stage, the mean of planting stock survival rate was 90.3±1.1% per genotype. The evaluated grapevine rootstocks present morphophysiologic parameters appropriated to in vitro propagation and ex vitro transference.